Evaluation of Microbiological Flora in Endo-Perio Lesions before and after Treatment - Hiroj Bagde; Rishiraj Singh Karki; Sajid Husain; Shahrukh Khan; Varanasi Haripriya; Prasoon Purwar (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Endo-perio lesions present a complex interplay between endodontic and periodontal infections, often leading to treatment challenges. The microbial flora associated with these lesions includes a diverse range of pathogenic bacteria contributing to disease progression. Evaluating changes in microbiological flora before and after treatment is crucial for assessing the efficacy of therapeutic interventions. Materials and Methods: A total of 30 patients diagnosed with endo-perio lesions were included in this study. Microbiological samples were collected from the lesion sites before treatment and after six weeks of therapy. The treatment involved root canal therapy combined with periodontal debridement and systemic antibiotic administration. Microbial analysis was performed using culture methods and polymerase chain reaction (PCR) to identify key bacterial species, including Porphyromonas gingivalis, Fusobacterium nucleatum, and Enterococcus faecalis. Statistical analysis was conducted using paired t tests to assess microbial reduction. Results: Before treatment, P. gingivalis was detected in 85% of cases, F. nucleatum in 75%, and E. faecalis in 60%. After treatment, the prevalence of these bacteria reduced significantly, with P. gingivalis detected in 30% of cases, F. nucleatum in 25%, and E. faecalis in 15% (P < 0.05). The reduction in bacterial load correlated with improved clinical parameters, including decreased pocket depth and reduced pain scores. Conclusion: The findings indicate that combined endodontic and periodontal therapy significantly reduces pathogenic microbial load in endo-perio lesions, leading to clinical improvement. Effective microbial control is essential for successful management, emphasizing the need for comprehensive treatment approaches.